2014
DOI: 10.2139/ssrn.2517496
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Benchmarks: When Do Crowds Provide Wisdom?

Abstract: We compare the performance of a comprehensive set of alternative peer identification schemes used in economic benchmarking. Our results show the peer firms identified from aggregation of informed agents' revealed choices in Lee, Ma, and Wang (2014) perform best, followed by peers with the highest overlap in analyst coverage, in explaining cross-sectional variations in base firms' out-of-sample: (a) stock returns, (b) valuation multiples, (c) growth rates, (d) R&D expenditures, (e) leverage, and (f) profitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Consistent with this idea, Lee, Ma, and Wang (2016) document that analysts cover economically similar or related stocks-the fundamentals of analyst co-covered stocks are highly correlated. Furthermore, they show 2 that analyst linkages explain the cross-sectional variation in firm returns and fundamentals better than traditional industry linkages.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Consistent with this idea, Lee, Ma, and Wang (2016) document that analysts cover economically similar or related stocks-the fundamentals of analyst co-covered stocks are highly correlated. Furthermore, they show 2 that analyst linkages explain the cross-sectional variation in firm returns and fundamentals better than traditional industry linkages.…”
Section: Introductionmentioning
confidence: 72%
“…Using a variety of proxies for interfirm linkage or relatedness, various papers have verified such spillovers. 1 This literature documents lead-lag relationships among stocks belonging to the same industry (Moskowitz and Grinblatt 1999), firms that share the same geographic location (Parsons, Sabbatucci, and Titman 2016), firms that are linked along the supply chain Frazzini 2008 andMenzly andOzbas 2010), firms with similar technologies (Lee, Ma, and Wang 2016), and single-and multi-segment firms operating in similar segments (Cohen and Lou 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schijven and Hitt [2012] analyzed the source of the wisdom of crowds and concluded that the buy-side crowd's attempt to assess managerial perceptions based on publicly available information leads to a vicarious form of wisdom. In economic benchmarking, Lee, Ma, and Wang [2014] displayed evidence that the wisdom of crowds results in peer identification schemes that systematically outperform standard classification schemes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The method developed and tested in this paper is used in Kaustia and Rantala (2015) to generate peer groups in a study of corporate peer effects involving stock splits. It has also been independently evaluated in a contemporaneous paper by Lee, Ma, and Wang (2016). They find that combining two recent approaches, one based on chronologically adjacent searches by the same individual performed on SEC's Electronic Data Gathering, Analysis, and Retrieval (EDGAR) system (Lee, Ma, and Wang (2015)) and the analyst-based method, is especially effective.…”
Section: Introductionmentioning
confidence: 99%